MOBILITAS NON PERMANEN MENJADI PILIHAN SEBAGIAN PEKERJA DALAM MENGHADAPI HIMPITAN EKONOMI DI WILAYAH DENPASAR, BADUNG, GIANYAR DAN TABANAN PROVINSI BALI 2014 - Putrawan I Wayan; Nindya Purnama Sari (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2015)
As an economic, business and government center in Bali Province, Denpasar, Badung, Gianyar and Tabananare well known as Sarbagita is the center of people attention, especially in trying to find a job. But the living costin destination area is more expensive than the place where they live, this is why they change their mobility patternfrom permanent mobility to non-permanent mobility. In last 4 years, there is about 14 percent of employee inSarbagita who work outside their residences. This percentage shown many people take economy benefits of mobility.But this situation is not always give an advantage, because of facilities and infrastructures are required to avoid areducing in economy benefit of mobility. We need information about characteristics of people who work by nonpermanentmobility around Sarbagita and also information about contribution and relationship form between peoplecharacteristics and their decision to work by non-permanent mobility. This information is used to identify the patternand needs of that employee. To seek further this information, it;s to be used National Labour Force Survey (Sakernas)August 2014 data and focused in employee who work by non-permanent mobility around Sarbagita. Descriptiveanalysis is used to seek information about characteristics of people who work by non-permanent mobility aroundSarbagita. Only 1.89 percent of them use public transportation as their daily transportation. We also use logisticregression analysis to find contribution and relationship form between people characteristics and their decision towork by non-permanent mobility. Male employee who work in service area with a younger age, a higher wage and ahigher education tend to decide working by non-permanent mobility around Sarbagita. Economy needs of marriedpeople does not give a significant contribution to decide working by non-permanent mobility around Sarbagita.